FAKTOR-FAKTOR YANG MEMPENGARUHI REMITAN DAN PRIORITAS PENGGUNAAN REMITAN (Studi Pada Keluarga Tenaga Kerja Indonesia di Desa Tanggulturus Kecamatan Besuki Kabupaten Tulungagung) - Muhammad Dhimas Pamungkas; Badriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Given the large number of Indonesian Workers (TKI) and also the potential for remittances that enter the Besuki sub-district. In addition, many studies have found that in general, TKI remittances are used for consumption purposes, so it is necessary to study the factors that influence remittances and the priority of using remittances in Tanggulturus Village. With several variables that have been determined, this study aims to: (1) To analyze the effect of education level, working time, and gender on the remittance level of TKI in Tanggulturus Village, Besuki District, Tulungagung Regency (2) To analyze how the priority of using TKI remittance funds in family economic activities. The place and time of this research are households in Tanggulturus Village, Tulungagung Regency in 2017. The analytical method used is multiple linear regression. The results showed that the variables of education level and length of work had a positive and significant effect on the number of remittances sent. While the gender variable has an effect but not significant. In the priority use of household consumption, migrants use (1) basic needs, (2) house renovation, (3) buying furniture, (4) buying vehicles, and finally (5) paying debts. Meanwhile, the priority of using migrant household investment is (1) saving, (2 and 3) buying land, (4) opening a business and lastly (5) buying livestock. Keywords : remittances, education, length of work, gender, consumption, investment